Pengaruh Kapabilitas Pemasaran Untuk Meningkatkan Keunggulan Bersaing Pada Masa Covid-19 - Mochammad Maulana Hasan Jaelani; R Deni Muhammad Danial; Asep Muhammad Ramdan (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The purpose of this study is to find out the impact of marketing capability on the competitive advantage in creative economy of photograph in Sukabumi city. The object of this study is the marketing capability and competitive advantage. The research method used is associative descriptive quantitative method which using statistical calculation to measure how big or small the impact of two free variables or more. The technique of data analysis begins with validity testing, reliability testing and normality testing. It is also supported by f-testing, multiple coefficient correlation, coefficient determination, multiple linear regression, and t-testing to determine the extent of the impact of both independent variables or free variable studied to the dependent variable or bound variable. Based on the result of the study, there is a significant impact of marketing capability on competitive advantage in the amount of 0.001 due to 0,001 < 0,05. From that result, it can be known that there is a significant advantage between marketing capability on competitive advantage. Keywords: Marketing Capability, Competitive Advantage